(untitled) (Journal of Technology and Operations Management, 2017)
The aim of this paper is to discuss how Learning Management System (LMS) is productive for students in higher education and their perception toward the LMS usage in their learning process. In detail, this paper clarifies the effectiveness of the LMS in higher education for the students and aid to realize the students’ perception on using the LMS for their learning process. There is some analysis regard the students’ perception on applying the LMS for their learning purpose. This paper approach the students thoughts and acceptance of LMS in higher education. The finding of this paper explores the origin, type, function and the advantage and disadvantage of LMS in higher education which may lead to know the students’ judgement about the LMS. This paper shows that how administration and instructors able to motivate the students in higher education to utilize the LMS usage in their learning process and expand the LMS application in secondary education. This paper provides some empirical evidence based on previous studies that LMS is a system which more suitable to be used in higher education to determine the students’ involvement; and students’ opinion regards the LMS usage in their learning process.